Comparação entre duas estratégias de controle do TCSC para mitigação de ressonância subsíncrona - Erlacher, Ronei (2016)
The capacitive series compensation is an economically viable alternative used in transmission lines to increase the power flow, that is, increase line capacity, in addition to increasing the stability limits of the electrical system. However, the inclusion of series capacitors in power lines can cause serious problems to the system, such as the Subsynchronous Resonance - SSR phenomenon, where, in the power system, the mechanical subsystem interacts with the electrical subsystem, below the synchronous frequency of the network, causing torques oscillations in the turbogenerators, which can be amplified, causing damage in the shafts of these machines. There are several alternatives for reducing the subsynchronous oscillations caused by the capacitive series compensation. Among these, we can mention the application of FACTS (Flexible Alternate Transmission System) devices, highlighting the TCSC (Thyristor Controlled Series Capacitor), which basically works as a controlled variable reactance, allowing the flexibility of the power system through a series compensation with continuous variation, in addition to its application as mitigating the effects of the SSR. The TCSC is the object of study in this work which is applied to the damping of subsynchronous oscillations in a basic system, proposed by the IEEE. This study is carried out by a physical-mathematical approach to SSR problem, as well as the theory and application of TCSC through two methods of control: NGH - SSR strategy and the constant power control strategy. Through simulation software you can see the SSR impacts on the power system. In the case of this work, it is used PacDyn, developed by the CEPEL for SSR studies, and PSCAD/EMTDC, for the simulation of electromagnetic transients. In addition, through the PSCAD/EMTDC software the control of TCSC is implemented adopting the methodologies cited, comparing them with each other and checking the affectivity of such strategies.